Fully Programmable Gaussian Function Generator Using Floating Gate MOS Transistor. (20th November 2012) - Srivastava, Richa; Gupta, Maneesha; Singh, Urvashi
Abstract : Floating gate MOS (FGMOS) based fully programmable Gaussian function generator is presented. The circuit combines the tunable property of FGMOS transistor, exponential characteristics of MOS transistor in weak inversion, and its square law characteristic in strong inversion region to implement the function. Two-quadrant current mode squarer is the core subcircuit of Gaussian function generator that helps to implement full Gaussian function for positive as well as negative input current. FGMOS implementation of the circuit reduces the current mismatching error and increases the tunability of the circuit. The performance of circuit is verified at 1.8 V in TSMC 0.18 μ m CMOS, BSIM3, and Level 49 technology by using Cadence Spectre simulator.